Ten years of the federal program “Bolsa-Atleta” (Athlete-Grant): a description of the paralympic sports (2005-2014) - Reis, Rafael Estevam (2015)
This article aims to make a description of an important federal program of development of Brazilian sport called "Bolsa-Atleta". Therefore, the source used in the analysis were the lists of contemplated athletes, available at the Sports Ministry's website, outlining the studies between the years 2005-2014. From these lists, only the information related to Paralympic modalities was used, with a total number of 7815 grants. In conclusion, the research shows that the "Bolsa-Atleta" prioritizes athletes with higher performance, males and those that represent the most economically developed regions.